School Teachers’ Perspectives on the Techniques Used in Teaching Sunrise Series 7-9 - Hakeem, Salam Neamah Hirmiz; Ahmed, Fryad Hussein (جامعة صلاح الدين, 2020)
هذه الدراسة التي هي بعنوان "وجهات نظر معلمي المدارس حول تقنيات المستخدمة في التدريس سلسلة سنرايز 7-9" تهدف إلى تقييم وجهات نظر معلمي اللغة الإنجليزية كلغة أجنبية حول التقنيات المستخدمة في تدريس هذا البرنامج. تم إجراء الدراسة على 52 معلما للغة الإنجليزية كلغة أجنبية حيث يقومون بتدريس اللغة الإنجليزية في 19 مدرسة تم اختيارها عشوائيا في مدينة أربيل. تم استخدام الطريقة الكمية لهذه الدراسة وتم جمع البيانات من خلال تحضير استبيان لمعلمي اللغة الإنجليزية كلغة أجنبية. كشفت نتائج الدراسة أن معلمي اللغة الإنجليزية كلغة أجنبية في المدارس الأساسية كانوا على دراية بتقنيات التدريس في برنامج سلسلة سنرايز7-9 ، لكنهم في الغالب استخدموا تقنيات التدريس التقليدية. كذلك يتفق غالبيتهم على أن تقنيات التدريس في سلسلة سنرايز 7-9 هي قابلة للتطبيق في الصف الدراسي. This paper is entitled “School Teachers’ Perspectives on the Techniques Used in Teaching Sunrise series 7-9”. It aims at assessing EFL Teachers' perspectives on the techniques used in teaching this program. It was conducted on 52 EFL teachers who teach English language in 19 schools which were chosen randomly in Erbil city. A quantitative method has been employed for this study and the data has been collected through a structured questionnaire for EFL teachers. The findings of the study revealed that the EFL teachers in basic schools were familiar with the teaching techniques in Sunrise series 7-9 program, but they mostly used traditional teaching techniques. Besides, they mostly agree that the teaching techniques in Sunrise series 7-9 are applicable in the classroom.
Keywords: أساسيات تعلم اللغة -- تعلم اللغة الإنجليزية -- مهارات التعلم -- طرق التدريس التقليدية